Cryoconcentrated soymilk and xanthan gum acted in stability of creamy sauce during storage (Research, Society and Development, 2021)
The formation of an emulsion with reduced lipid content can cause instability in the product during storage, requiring adaptations in the formulation. The objective of this work was to analyze the stability of the creamy sauce of cryoconcentrated soymilk stored for 60 days. The creamy sauce was prepared and packed in polyethylene bottles, sealed with aluminum seals and kept at room temperature. In physicochemical analyzes was noticed that the proteins and ashes were similar in all the samples and small differences in moisture and lipids contents, the pH remained below 4.0 and the beginning of the lipid oxidation was not verified in the follow-up period. The color of sauce showed slight differences during storage, but it remained a clear food, with yellow and green color. The microstructure of creamy sauce stored for two months was not altered, presenting polydisperse structures, packed and very close. Thus, the efficiency of the associated use of soy proteins and xanthan gum in the formation and stabilization of the emulsion for 60 days was proven. Therefore, this creamy sauce can be an alternative to increase the consumption of soy proteins, in food with half the lipid level when compared to the traditional ones.